Effect of superheated steam treatment of carbon fiber on interfacial adhesion to epoxy resin. (June 2016) - Wada, Masashi; Kawai, Kazuhiko; Suzuki, Tomoyuki; Hira, Hirohito; Kitaoka, Satoshi
Abstract: To elucidate the effect of superheated steam (SHS) treatment of carbon fiber on the adhesion to epoxy resin and surface states, virgin unsized carbon fiber was exposed to SHS with or without N2 in the temperature range of 500–800 °C. The interfacial shear strength (IFSS) between the carbon fiber and epoxy resin was successfully improved by SHS treatment with N2, and the IFSS of fiber treated above 700 °C was the same as or higher than that of a commercial sized fiber. SHS treatment without N2 resulted in an increase of total acidic groups on the fiber surface accompanied with the increase of phenolic hydroxyl groups, whereas that with N2 resulted in a simultaneous increase of total acidic and basic functional groups. The significant improvement in the IFSS after SHS treatment with N2 is considered to be due to the increase of basicity on the fiber surface.